Czynniki mające wpływ na podejmowanie decyzji o posiadaniu dziecka przez potencjalnych rodziców. Analiza pieniężnych i niepieniężnych kosztów oraz zysków z posiadania dziecka - Laszewska-Hellriegel, Martyna (Wydawnictwo Naukowe UAM, 2011)
The article deals with the problem of decision making process of potential parents to become a child. The starting point is the behaviour model of Homo Oeconomicus, who after consideration of all pros and cons chooses the alternative which is the most profitable for him. After a short theoretical introduction, showing the research status on this field, article concentrates on the profits and losses of having the child. And so first are shown all financial and non financial gains of having a child and than the financial and non financial looses. On the end of the article the author shows also other factors which influence the decision taking model. This analysis can be useful by policy making in the countries willing to influence the birth rate.
Factors influencing the decision-making process of having a child by potential parents. A financial and non-financial analysis of costs and benefits of having a child